Unusual Enthalpy Driven Self Assembly at Room Temperature with Chitosan Amphiphiles - Odunze, Uchechukwu; O'Brien, Fionn; Godfrey, Lisa; Schätzlein, Andreas; Uchegbu, Ijeoma (Pharmaceutical Nanotechnology, 2019)
Background: GCPQ (N-palmitoyl-N-monomethyl-N,N-dimethyl-N,N,N-trimethyl- 6-O-glycolchitosan) is a self-assembling polymer being investigated as a pharmaceutical nano-carrier. GCPQ nanoparticles shuttle drugs across biological barriers, improving drug performance. The exact chemistry of GCPQ is varied by the relative proportion of hydrophobic (N-palmitoyl) and hydrophilic (quaternary ammonium) groups and molecular weight. Objective: We hypothesised that the thermodynamics of self-assembly is controlled by the polymer molecular weight and hydrophobicity. Method: The thermodynamics of self-assembly was investigated using isothermal calorimetry. Results: GCPQs (Mw = 8-15 kDa) formed micellar aggregates at critical micellar concentrations of 1-2.4 μM at 25°C and micellisation was unusually enthalpy driven. There was a positive correlation between ΔHmic and mole% quaternary groups (Q): ΔHmic = 3.8 Q- 159 (r2 = 0.93) and a negative correlation between ΔHmic and molecular weight (Mw): ΔHmic = -13.5 Mw-26.3 (r2 = 0.99). Conclusion: These findings provide insights into the positive drivers of stable selfassemblies, namely hydrophobicity and molecular weight, as both hydrophobicity and molecular weight are associated with an increased enthalpy contribution to micellisation.
Keywords: polymer